INCIDÊNCIA DE ANOREXIA E DESNUTRIÇÃO ENTRE INDÍGENAS IDOSOS RESIDENTES EM CONTEXTO URBANO, EM CAMPO GRANDE – MS. - VILLALBA, Daniel Lucas Lopes Freitas,; ALMEIDA, Isis Marcondes Sodré de,; AQUINO, Rayra Jordania Freire,; BIANCHI, Melissa Wohnrath,; QUADROS, Fatima Alice Aguiar,; SACCO, Carolina Maria Startari, (ANAIS DO ENIC, 2023)
-